An Investigation of Illegal Downloading of Music in Western Malaysia - Bashir, Shakeil; Phau, Ian; Ferguson, Graham (Australian and New Zealand Marketing Academy, 2012)
This empirical study investigates the phenomenon of illegal downloading behaviour of Malaysian individuals. 434 usable responses were used in the analysis. This paper uses the theory of planned behaviour as the theoretical framework for the study. Key constructs include attitudes towards music piracy, attitude towards lawfulness, susceptibility to interpersonal influence, facilitating conditions as antecedents towards downloading intention and ultimately downloading behaviour. A number of implications for businesses will be discussed, suggestions for future research are reviewed and the main contributions of the study will also be delineated.